2015
DOI: 10.1161/circulationaha.114.011732
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Therapy in Individuals With Prehypertension or Hypertension

Abstract: V itamin D deficiency is a common problem with implications for human health.1 A large body of epidemiological evidence links vitamin D deficiency with a higher risk of cardiovascular disorders, including hypertension. 2,3A meta-analysis of observational studies found that every 16-ng/mL decrease in vitamin D was associated with a 16% higher risk of hypertension. 4 A meta-analysis of population genetic studies suggested that polymorphisms related to Background-A large body of epidemiological and experimental e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(58 citation statements)
references
References 27 publications
6
45
1
6
Order By: Relevance
“…A recent meta-analysis on a large number of studies found no evidence of vitamin D supplementation on BP reduction (40). Also, two recent RCT in hypertensive patients with low 25(OH)D 3 levels did not find a significant effect of vitamin D supplementation on BP (24,365). Together, these findings do not support the use of vitamin D as treatment for hypertension.…”
Section: Iii) Randomized Control Trialsmentioning
confidence: 82%
“…A recent meta-analysis on a large number of studies found no evidence of vitamin D supplementation on BP reduction (40). Also, two recent RCT in hypertensive patients with low 25(OH)D 3 levels did not find a significant effect of vitamin D supplementation on BP (24,365). Together, these findings do not support the use of vitamin D as treatment for hypertension.…”
Section: Iii) Randomized Control Trialsmentioning
confidence: 82%
“…Generally, most of the effective trials were of a smaller sample size. Seven RCTs with an apparently appropriate sample size have investigated the effects of VitD on brachial BP, and from these, 6 reported no significant improvement [68,76,77,92,93,94]. Only 1 trial reported significant BP lowering, and this was in a population of black individuals [79]; importantly though, this effect was no longer significant after correcting for between-group differences in BP at baseline.…”
Section: Critical Factors To Consider Regarding the Interpretation Ofmentioning
confidence: 99%
“…The remaining 73% of studies placed no restrictions on baseline serum VitD levels or included a combination of deficient and non-deficient participants (i.e., <30,<40 or <60 ng/ml), which could confound the results. Among the RCTs that included VitD-deficient participants and investigated the effects on brachial BP (n = 8), 6 had no significant effects [64,70,71,77,85,94] and 2 (very short-term; ≤3 months) trials reported an improvement in brachial BP [56,60] (Table 1). None of the RCTs appropriately addressing rule 1 found a significant effect on cfPWV [64,70,71,77,84,85], carotid-radial PWV [75] or brachial-ankle PWV [64].…”
Section: Critical Factors To Consider Regarding the Interpretation Ofmentioning
confidence: 99%
“…However there were also trials that showed no effect of vitamin D supplementation on BP. One of them was performed by Arora et al The authors enrolled population of 534 patients aged between 18 and 50 with vitamin D deficiency, but only 28% of them were hypertensive [20]. The strength of this trial was that the patients didn't take antihypertensive drug, but on the other hand, the patients were young and mostly normotensive.…”
Section: Discussionmentioning
confidence: 99%